The Orientations of Large Aspect‐Ratio Coiled‐Coil Proteins Attached to Gold Nanostructures. Issue 11 (21st January 2016) - Chang, Jae‐Byum; Kim, Yong Ho; Thompson, Evan; No, Young Hyun; Kim, Nam Hyeong; Arrieta, Jose; Manfrinato, Vitor R.; Keating, Amy E.; Berggren, Karl K.
Abstract : Methods for patterning biomolecules on a substrate at the single molecule level have been studied as a route to sensors with single‐molecular sensitivity or as a way to probe biological phenomena at the single‐molecule level. However, the arrangement and orientation of single biomolecules on substrates has been less investigated. Here, the arrangement and orientation of two rod‐like coiled‐coil proteins, cortexillin and tropomyosin, around patterned gold nanostructures is examined. The high aspect ratio of the coiled coils makes it possible to study their orientations and to pursue a strategy of protein orientation via two‐point attachment. The proteins are anchored to the surfaces using thiol groups, and the number of cysteine residues in tropomyosin is varied to test how this variation affects the structure and arrangement of the surface‐attached proteins. Molecular dynamics studies are used to interpret the observed positional distributions. Based on initial studies of protein attachment to gold post structures, two 31‐nm‐long tropomyosin molecules are aligned between the two sidewalls of a trench with a width of 68 nm. Because the approach presented in this study uses one of twenty natural amino acids, this method provides a convenient way to pattern biomolecules on substrates using standard chemistry. Abstract : Two coiled‐coil proteins with different lengths (cortexillin and tropomyosin) are attached to gold nanostructures via cysteine–gold interaction and their arrangements are studied. The structures change upon protein denaturation. Single‐point attachment of rod‐like coiled coils is used to align proteins with respect to a two‐walled nanotrench.